Evaluating and Improving the Budget Absorption in the Human Resource Development Agency of Ministry Energy and Mineral Resource - Supriyanto, Teguh; Sunitiyoso, Yos (The Indonesian Journal of Business Administration, 2017)
Abstract. Implementation of activities and budgets in the HRDA-EMR has not been in line with expectations. One indication is the absorption of the budget that has not reached the set target and is still concentrated at the end of the budget year. Budget absorption is one indicator that can indicate the success of the program or policy conducted by the HRDA-EMR. By using qualitative descriptive method, this research is intended to analyze the factors that influence budget absorption. This study found that planning, administration and regulatory factors were the main factors affecting budget absorption in all work units at the HRDA-EMR. Good planning and supported by an organized administration will greatly help the level of budget absorption. In addition, internal control system is required from the beginning of planning in order to detect the possibility of early budget absorption failure. Internal control system also has an important role to know the development of budget absorption. Meanwhile, to speed up the absorption of state budget, it is necessary to monitor the control through monitoring and evaluation of activity and budget routinely so that all problems and obstacles during the implementation process of the budget can be found solution and its solution.Keywords: Absorption, Budget, internal control system, monitoring and evaluation